Assessment of possibilities of detection and tracking of drones the system of radiolocation stations of antiaircraft defense - Herasimov, S. V.; Kukobko, S. V.; Roshchupkin, E. S.; Roshchupkina, A. E. (НТУ «ХПІ», 2020)
The report examined the capabilities for detecting and tracking drones when combining existing air defense radar into a system. The effective scattering surface of drones was calculations into account for the operating wavelengths of individual radars included in the system. The obtained values were used to calculate the characteristics of the detection and tracking of drones by a multi-position radar system. The expediency of using the proposed solutions for typical battle order schemes is shown taking into account the positions of radar of the air defense systems.
Keywords: air defense; drone; radar